JURIDICAL REVIEW OF INHERITANCE PROPERTY DISPUTES REVIEWED FROM NIAS CUSTOMARY LAW CASE STUDY: GUNUNGSITOLI STATE COURT RULING NO. 84/PDT.G/2021/PN GST - Analisman Zalukhu; Bambang Fitrianto; Siti Nurhayati (PT. Radja Intercontinental Publishing, 2024)
The distribution of inheritance in Indonesia is not the same between one community group and another. This difference arises because the inheritance distribution system according to customary law rules is closely related to the family system that applies to each community group itself. Division of inheritance often results in sDisputes can be caused by various factors, including differences of opinion or disagreements between one party and another, and can also be caused by the dominance of the oldest heir or male children who get more of the inheritance. In fact, many cases and disputes over inheritance of inheritance between fellow heirs have reached court and have even been decided by the court. This research usesnormative juridical research methods, using a qualitative approach.The type of data in this research was collected by applying the library research method with secondary data sources and enriched with primary data resulting from interviews with a Nias traditional community leader.Based on the research, the results showed that the Nias traditional community in dividing inheritance property draws on the male lineage, where in this case sons and daughters follow the father's lineage or a system of paternal descent (Patrilineal) is applied, which is based on blood ties according to father's line, so that only sons are heirs, because daughters are considered to have left their father's family, if they are married. Land status in dispute case no. 84/Pdt.g/2021/PB Gst is the land inherited from the late. Badukhali Zega bint Sarinata.The results of the research show that the judge's considerations which caused the lawsuit to be rejected in its entirety were because the Plaintiffs were unable to prove the arguments for their lawsuit with valid arguments, whereas on the other hand the Defendants had succeeded in proving their objections, so the Plaintiffs' lawsuit was appropriate and had legal grounds to be rejected in its entirety.